Management of Gamma-Butyrolactone Dependence with Assisted Self-Administration of GBL - Rafael Meyer; Josef Jenewein; Soenke Boettger (Case Reports in Neurological Medicine)
Gamma-hydroxybutyric acid (GHB) and its liquid precursor gamma-butyrolactone (GBL) have become increasingly popular beyond the clubbing culture resulting in daily consumption and dependence in the broader population. This case report illustrates the challenges of managing GHB-withdrawal and a possibly superior future approach of its management by titration and tapering of the addictive agent.